2020
DOI: 10.1029/2019jd031796
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tropical Cyclone Landfall Angle on Storm Surge Along the Mid‐Atlantic Bight

Abstract: Storm surge impact depends on coastal geographical and bathymetric features as well as various tropical cyclone characteristics including the size, intensity, and impact angle of the storm. Although the factors contributing to storm surge are well studied, uncertainties remain regarding the level of sensitivity to these parameters. This work seeks to contribute to the current knowledge of storm surge by studying the sensitivity to tropical cyclone landfall angle. We perform an ensemble of synthetic tropical cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…In this section, we briefly describe the atmospheric and hydrodynamic data sets used to train the ANN model. The data sets are publicly available through the DesignSafe‐CI repository, published as Ramos‐Valle (2019). We also discuss the design of the ANN model, the metrics used to evaluate the storm surge predictions, and the methods used to analyze the neural network and the individual contributions of the input variables in accurately forecasting storm surge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we briefly describe the atmospheric and hydrodynamic data sets used to train the ANN model. The data sets are publicly available through the DesignSafe‐CI repository, published as Ramos‐Valle (2019). We also discuss the design of the ANN model, the metrics used to evaluate the storm surge predictions, and the methods used to analyze the neural network and the individual contributions of the input variables in accurately forecasting storm surge.…”
Section: Methodsmentioning
confidence: 99%
“…Storm surge magnitude is a function of various TC characteristics and physical parameters, including the cyclone intensity (Weisberg & Zheng, 2006), size (Irish et al., 2008), and forward speed (Hussain et al., 2017; Rego & Li, 2009; Thomas et al., 2019). Recent studies have also shown the dependency of storm surge on cyclone landfall angle and impact location (Bloemendaal et al., 2019; Ramos‐Valle et al., 2020). In this study, we explore questions such as: (a) What is the relative importance of each cyclone parameter in determining storm surge?…”
Section: Introductionmentioning
confidence: 99%
“…Our results may be influenced by moderate differences in tracks of the CTRL and PGW simulations, which can have important implications for landfall location and angle of approach. Perpendicularly landfalling storms tend to produce more wide spread surges than those that make landfall diagonally, however this is rare (Hall and Sobel, 2013;Ramos-Valle et al, 2020). Also, in some areas, track fluctuations lead to landfalls of areas with different physical characteristics of the coastline and shelf that can either amplify or diminish surge magnitude (Azam et al, 2004;Mori et al, 2014).…”
Section: Influence Of Storm Characteristicsmentioning
confidence: 99%
“…Historically, it has been assumed that storm surge is directly and solely related to hurricane intensity, i.e., maximum sustained wind speed and minimum central pressure. However, over time, historical evidence and research have shown that other meteorological properties of hurricanes including size, translation speed, and angle of approach, as well as geophysical characteristics of impacted areas (e.g., coastal geography, topography, and bottom friction) have significant impacts on the generation and propagation of storm surges (Irish et al, 2008;Li, 2009, 2010;Resio et al, 2009;Irish and Resio, 2010;Weaver and Slinn, 2010;Mayo et al, 2014;Needham and Keim, 2014;Akbar et al, 2017;Fossell et al, 2017;Thomas et al, 2019;Ramos-Valle et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) used ROMS forced with meteorological forcing obtained from the U.S. National Centers for Environmental Prediction Climate Forecast System Reanalysis to simulate SSL along the Australian coastline. The process‐driven hydrodynamic models contribute to the understanding of physical mechanisms of the storm surge process and can predict storm surges accurately (Dietrich et al., 2011; Ramos‐Valle et al., 2020); however, they are often numerically expensive and may fail to fully resolve bathymetric and geometric features due to limited details in the available data sets or the resolution of computational grids, thereby affecting the applicability and accuracy of the SSL simulation (Arns et al., 2020; Beisiegel et al., 2020; Cyriac et al., 2018; Fernández‐Montblanc et al., 2019; Zou et al., 2013).…”
Section: Introductionmentioning
confidence: 99%